Efficient and effective removal of emerging contaminants through the parallel coupling of rapid adsorption and photocatalytic degradation: A case study of fluoroquinolones. (October 2021) - Zhang, Qi; Zhu, Zijian; Zhao, Xiaoyang; Xiao, Xin; Zuo, Xiaoxi; Nan, Junmin
Abstract: The development of efficient, effective, and large-scale treatment methods to address high-risk emerging contaminants (ECs) is a growing challenge in environmental remediation. Herein, a novel parallel coupling strategy of adsorption separation and photodegradation regeneration (parallel ASPR) is proposed; subsequently, an adsorptive photocatalyst (Zn-doped BiOI) is designed to demonstrate how to effectively eliminate fluoroquinolones (FQs) from water with the proposed ASPR scheme. Compared with pure BiOI, the addition of Zn 2+ during synthesis has a significant influence on the morphology and structure of the products, resulting in Zn-doped BiOI samples with up to 5 times the specific surface area, 32 times the adsorption capacity, and 20 times the photocurrent intensity. The optimized Zn-doped BiOI sample has an excellent adsorption efficiency for FQs with a removal rate that exceeds 95% after 5 min of adsorption for all 6 tested FQ antibiotics. Then the adsorbed contaminants can be effectively degraded during the later visible-light irradiation process, and the adsorbent can be regenerated synchronously, showing excellent ASPR cycling performances. The mechanisms of rapid adsorption and photocatalysis were explored via material characterizations, adsorption models, density functional theory calculations, and photogenerated species analyses. The results reveal that the enhanced adsorption of Zn-doped BiOI for FQs is due to its high specific surface area, coordination-based chemical adsorption, and surface electrostatic attraction, while its superior visible-light photodegradation performance is mainly ascribed to its strong redox ability, abundant surface oxygen vacancies, and enhanced photogenerated carrier separation efficiency. Graphical abstract: Image 1 Highlights: Parallel coupling of adsorption separation and photodegradation regeneration is proposed. An adsorptive photocatalyst Zn-doped BiOI was synthesized by a rapid microwave route. Zn-doped BiOI exhibits high capacity and fast kinetics for fluoroquinolones adsorption. Pollutant can be degraded by photocatalytic process while adsorbent can be regenerated. The mechanisms are studied by experiments, theoretical models, and DFT calculations.